2014
DOI: 10.1038/ncomms6229
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of Nafion layers in fuel cell electrodes

Abstract: Proton exchange membrane fuel cell is one of the most promising zero-emission power sources for automotive or stationary applications. However, their cost and lifetime remain the two major key issues for a widespread commercialization. Consequently, much attention has been devoted to optimizing the membrane/electrode assembly that constitute the fuel cell core. The electrodes consist of carbon black supporting Pt nanoparticles and Nafion as the ionomer binder. Although the ionomer plays a crucial role as ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
271
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(288 citation statements)
references
References 33 publications
16
271
0
1
Order By: Relevance
“…Different analysis methods were used for detection of ionomer size in electrodes. 19,35,36 In catalytic layers of fuel cells an operation-induced thinning of the ionomer films that partly encapsulate the platinum covered carbon (Pt/C) agglomerates has been reported. 13,37,38 The observed stronger thinning of the ionomer layers in the anode at samples cut close to the hydrogen inlet and with the use of thin membranes was explained by the higher concentration of highly active hydrogen radicals.…”
Section: F3140mentioning
confidence: 99%
“…Different analysis methods were used for detection of ionomer size in electrodes. 19,35,36 In catalytic layers of fuel cells an operation-induced thinning of the ionomer films that partly encapsulate the platinum covered carbon (Pt/C) agglomerates has been reported. 13,37,38 The observed stronger thinning of the ionomer layers in the anode at samples cut close to the hydrogen inlet and with the use of thin membranes was explained by the higher concentration of highly active hydrogen radicals.…”
Section: F3140mentioning
confidence: 99%
“…Thus, the catalyst layer resistance can be obtained from EIS spectra at any potential although we advocate the use of reducing potentials under N 2 for facile extraction of R H + ,cl-eff . The effective protonic conductivity of the catalyst layer is anticipated to be dominated by the conductivity of 0.1 M HClO 4 since the ionomer (nm thickness [112][113][114][115] ) is soaked in it. 75 Since R H + ,cl-eff is directly proportional to the acid conductivity (hence acid molarity) it confirms our interpretation that the real intercept of the Nyquist plot does indeed provide a measure of the catalyst layer resistance.…”
Section: Eis-catalyst Layer Protonic Resistance (R H + CLmentioning
confidence: 99%
“…[9][10][11][12][13][14] These have been rationalized by suggesting more complex oxygen reduction reaction (ORR) kinetics with variable Tafel slope, 4 by an interfacial resistance at the ionomer/platinum interface, 9,15 and/or by unusually high oxygen transport resistances through an assumed homogeneous thin ionomer film covering the Pt particles. 16,17 However, recent high-resolution transmission electron microscopy studies suggested that the ionomer coverage in the electrode may be rather inhomogeneous 18 and that the solvents used for preparing catalyst inks for electrode preparation influence the ionomer distribution in the final electrode, which in turn affects MEA (membrane electrode assembly) performance. 19 Therefore, one of the challenges in preparing MEAs is to achieve catalyst layers with a homogeneous ionomer distribution.…”
mentioning
confidence: 99%